2003
DOI: 10.1002/pbc.10436
|View full text |Cite
|
Sign up to set email alerts
|

Leukemic cells and the cytokine patchwork

Abstract: Since hematopoietic growth factors are present in high serum concentrations in patients with acute leukemia and myelodysplastic syndromes, consequences of possible interactions should be kept in mind even when well-defined human recombinant factors in single application are to be involved in antileukemic protocols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 98 publications
(128 reference statements)
1
14
0
Order By: Relevance
“…In particular, γ interleukins were reported to have proliferative and differentiating effects on T-ALL primary cells (77). Despite the differences between normal blood stem cells and malignant ones, they both use cytokine signaling for progression and differentiation (78). Our analysis predicted IL8, IL9 and the IL2 receptor.…”
Section: Cytokine/cytokine Interactionsmentioning
confidence: 96%
“…In particular, γ interleukins were reported to have proliferative and differentiating effects on T-ALL primary cells (77). Despite the differences between normal blood stem cells and malignant ones, they both use cytokine signaling for progression and differentiation (78). Our analysis predicted IL8, IL9 and the IL2 receptor.…”
Section: Cytokine/cytokine Interactionsmentioning
confidence: 96%
“…Aguayo et al (23) have shown that VEGF-A and related growth factors enhance the bone marrow microvasculature in bone marrow biopsies in relapsed leukemia patients. Quiescent residual leukemia stem cells may also be stimulated into cell replication by VEGF-A and other growth factors (2,4,5,9,12,15,23,24,31,39,40).…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon seemed to correlate with cellular drug resistance to anthracyclines. In leukemia, the clonal population is characterized by a hierarchical organization similar to the normal hematopoiesis and a subset of the stem cells retain their undifferentiated ''stem cell'' morphology (2). The cytokine effect on acute lymphoblastic leukemia (ALL) stem cells, especially childhood T-cell ALL cells, seems to be similar to normal hematopoietic bone marrow cells.…”
mentioning
confidence: 99%
“…One of the genetic factors may be an aberration of cytokine regulation and cytokine production, which can lead to an increased apoptosis of hematopoietic progenitor cells, and aberrant hematopoiesis. The excessive production of growth-inhibitory cytokines such as TNF-␣ in patients with MDS has been described [3,4,29] . Recent data indicate that TGF-␤ inhibits myeloid, erythroid, megakaryocytic and multilineage colony formation [5][6][7] .…”
Section: Discussionmentioning
confidence: 99%
“…A number of investigators have demonstrated an excessive production of proapoptotic cytokines in the bone marrow of MDS patients. Several studies have stressed the im portance of increased levels of tumor necrosis factor-␣ (TNF-␣ ) in the serum and bone marrow in promoting apoptosis [3,4] . Transforming growth factor-␤ (TGF-␤ ) is another cytokine which is generally considered to be a negative key regulator of hematopoietic stem and progenitor cells [5][6][7] .…”
Section: Introductionmentioning
confidence: 99%